Seventh Evaluation Report - Planning Commission (Planning Commission, 1960)
The present report, the Seventh Evaluation Report is, in more than one sense, a departure from its predecessors. In the first place, it contains studies other than evaluation studies. There are two sets of case studies of successful panchayats and cooperatives and also a fragmentary study of rural unemployment. All these studies throw light on important problems with which the C.D. programme is concerned; but they have not been prepared from the point of view of what contribution the programme may have made to their solution. Secondly, of the two evaluation studies incorporated in the present report, only one seeks to evaluate the operation of the C D. programme. The other is made up of three separate evaluations of the winter crop campaign in the States of Punjab, Rajasthan, and UP. in the year 1958-59. These are, of course, all evaluation studies and they deal with the most important aspect of rural development viz. the expansion of agricultural output, on which the C.D. programme correctly places the greatest emphasis. But they are, again. not evaluations of the C.D. programme as such.
Community Development and Some Allied Fields